How Internal Customer Relationship Management and Word of Mouth, Affect Customer Loyalty - Linus Jonathan Vem; Joy Philip Mshelmbula; Abel Daniel Ochigbo; Ruth Agwom-Panle (Faculty of Economic and Business, 2024)
Originality: The competition in the banking industry has necessitated a concerted effort to ensure a sustainable internal and external customer relationship. Studies that focus on the internal customer relationship and internal customers’ word of mouth on external customer loyalty is rareObjective: This study investigates how Employees' Positive Word of mouth (PWoM) mediates the relationship between internal customer relationship management (IntCRM) and external Customer Loyalty (CL) using social exchange and image theoryMethodology: A cross-sectional research design was used, and a sample of 384 customers was drawn from an unknown pool of customers to respond to the CL questionnaire, while 315 bank employees responded to the IntCRM and PWoM Questionnaires. A partial least approach to structural equation modelling technique, via SMART-PLS version 4. was deployed to analyze the hypothesized relationships.Results: Findings on the direct relationship between IntCRM and CL were not supported due to insufficient evidence. While indirect relationships were established through the mechanism role of PWoM, supporting our argument that social exchange between employer and employee stimulates a positive attitude that attracts external customersImplications: The findings suggest the importance of relating discretely with the internal customer, since their perceptions and behaviours can influence the external customers’ attitudes towards the organization. The study also integrates the boundary of Human Resource Management (HRM) practice with Marketing strategy in ensuring customer loyalty in the banking industry. JEL Classification: M5, M31How to Cite:Vem, L. J., Mshembula, J. P., Ochigbo, A. D., Agwom-Panle, R., (2024). How Internal Customer Relationship Management and Word of Mouth Affect Customer Loyalty. Etikonomi, 23(1), 81 – 92. https://doi.org/10.15408/etk.v23i1.26921.